(untitled) (Perner’s Contacts, 2015)
The paper deals with an issue of the impact of contract form choice on providing public transport services and its influence on a scope of transport services. The first part describes a current situation in selected countries and then the possible contract forms with identifying existing risks are analysed. Further part of the paper describes an approach of public service operators within individual contract forms.